2022
DOI: 10.3389/fpsyg.2022.1040218
|View full text |Cite
|
Sign up to set email alerts
|

Follow or not? Descriptive norms and public health compliance: Mediating role of risk perception and moderating effect of behavioral visibility

Abstract: In a pandemic context, public health events are receiving unprecedented attention, and identifying ways to enhance individual public health compliance behaviors has become an urgent practical problem. Considering that individual decisions are susceptible to group members’ behaviors and that descriptive norms provide social information about the typical behaviors of others, we focused on the effects of the properties and reference groups of descriptive norms on public health compliance behaviors. We also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Research has also demonstrated that increasing feelings of hopefulness can help overcome fear of death from organ donation, and promote willingness to register as a donor [ 32 ]. Interventions could target descriptive norms either by highlighting the prevalence of organ donor registration within reference groups [ 62 ] or increasing the visibility of organ donor registration behavior—when a behavior is easily observed, individuals are more likely to construe that behavior as normative [ 63 , 64 ]. Interventions to increase prototype similarity could invite participants to identify with organ donors.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also demonstrated that increasing feelings of hopefulness can help overcome fear of death from organ donation, and promote willingness to register as a donor [ 32 ]. Interventions could target descriptive norms either by highlighting the prevalence of organ donor registration within reference groups [ 62 ] or increasing the visibility of organ donor registration behavior—when a behavior is easily observed, individuals are more likely to construe that behavior as normative [ 63 , 64 ]. Interventions to increase prototype similarity could invite participants to identify with organ donors.…”
Section: Discussionmentioning
confidence: 99%
“…This encompasses a broad spectrum of practices and attitudes aligned with established public health guidelines and regulations. The primary objective of such compliance is to maintain and improve community health, as highlighted in the study by Zhang et al (2022). Compliance in public health extends beyond mere adherence to health recommendations; it includes understanding and supporting the underlying principles of public health policies.…”
Section: Public Health Compliance and Vote Choicementioning
confidence: 99%
“…Medical care avoidance can result in delayed screening, missed opportunities for optimal recovery, increased risk of developing a serious disease, increased family care burden, increased medical care costs [ 1 4 ], and eventually, a decrease in the healthcare condition, quality of life, and life satisfaction of the population, particularly those with chronic diseases [ 3 , 4 ]. In 2021, 15.3% of Chinese chronic disease patients (including heart and chronic respiratory diseases, cancer, and diabetes), aged 30–70 years, suffered premature mortality due to medical care avoidance behavior (chronic diseases) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%